SYSTEM DESIGN THE PRICE OF GOODS AT PT SENDANG BUNDA - Yulianti Yulianti; Ir Rafael A. Gafar (Jurnal Sistem Informasi, 1999)
computerization system within a company can generate reports with a faster time, and save time, generate more accurate reports, and provide facilities in the process of re-search data if needed at any time.